Influence of restaurant attributes towards perceived value and customer overall satisfaction at casual dining restaurants in Klang Valley - Ahmad, Faridah; Ghazali, Hazrina; Othman, Mohhidin; Jules, Nathalie Joan (IDOSI Publications, 2017)
Casual dining restaurant becomes popular, especially among urban people in Malaysia which provides variety of menu in a comfortable environment with good services while the price offered is less expensive compare to fine dining restaurant. In order to identify the worthiness feeling dining at a casual dining restaurant, this study aimed to investigate the relationship between restaurant attributes towards perceived value. The relationship between perceived value and customers’ overall satisfaction were also measured. A total of 682 usable responses from casual dining restaurant customers in the Klang Valley were analysed. An exploratory factor analysis and inferential statistics procedure were performed by using SPSS Version 21. Moderate impacts with positive correlation were found between service attributes, food attributes and physical environment with perceived value. Interestingly, innovative and convenience attributes were also found to have correlation with perceived value. In addition, the relationship between perceived value and overall satisfaction was also found to have a moderate impact. The paper indicates that restaurant attributes have an impact to customers’ perceived value which ultimately leads to customers’ overall satisfaction.